A comprehensive experimental investigation of the rate-dependent interlaminar delamination behaviour of CFRP composites - Chen, Y; Liu, K; Xu, Z; Liu, H; Lißner, M; Erice, B; Petrinic, N (Elsevier, 2023)
The paper presents a systematic experimental study of the interlaminar delamination behaviour of a carbon composite subjected to Mode I, Mode II and Mixed-mode delamination at both quasi-static (QS) and high-rate (HR) conditions, which were conducted on a screw-driven test machine and in-house Hopkinson bar systems, respectively. A methodology integrating digital image correlation and the compliance-based beam theory was employed to circumvent the challenges in measuring the loads at HR tests and maintain good consistency during the data analysis of all delamination tests. The results demonstrated a positive rate-dependent delamination behaviour, with the HR Mode I, Mode II and Mixed-mode fracture toughness properties being 1.56, 1.66 and 1.60 times their QS counterparts, respectively. The cause of such a dependency was revealed following a detailed fractographic analysis, which highlighted that the observed dependency was associated with the transition of the predominant failure mechanisms in the QS and HR conditions.